Impacts of the use of long-term reversible contraceptive devices on women's health (Research, Society and Development, 2021)
The goal of this study was to carry out a systematic prism review using the prism technique that allowed us to identify the main health problems caused in women who used long-term reversible contraceptive devices. In the adopted methodology, the articles were selected through a process of 04 hierarchical levels, using cutoff criteria. At the first level, 1391 articles published between 2017 and 2021 were selected, in the SciELO, Academic Google, PubMed/MEDLINE and Virtual Health Library (Biblioteca Virtual de Saúde-BVS)/LILACS databases, using keywords as criteria. At the following levels, articles that contained themes, titles and abstracts related to the work were selected. After selection and screening, there was a reduction in the number of articles to 50 selected, representing 3.59% of the total, with PubMed/MEDLINE with 40 articles being the platform with the highest participation, corresponding to 2.88%. The other platforms presented the following values: SciELO 02 articles (0.14%); Academic Google and LILACS 04 articles each (0.28%). The main health problems and incidences in the platforms were also identified: bleeding (PubMed/MEDLINE 20%; LILACS and Google academic 4%); weight gain (PubMed/MEDLINE 16%; BVS/LILACS 4%); subdermal implant migration (PubMed 28%); influence on sexual function (PubMed/MEDLINE 6%); others (PubMed/MEDLINE 28%; BVS/LILACS 14%). It was found that the main health problems reported were bleeding and implant migration. Therefore, this reviews the main types of health problems caused by reversible contraceptive devices of long duration, in a short period of time, without compromising the accuracy of the results.